We never win where it counts: Sportswashing, law, and 'freedom' in post-1994 South Africa (Alternate Horizons, 2024)
On the dawn of democracy President Mandela utilized the South African team's victory in 1995 Rugby World Cup as a means to unite the nation. This was followed by the euphoria that followed with Bafana Bafana's win of the AFCON tournament.  This piece dissects whether this is a form of sportswashing and how sportswashing may not be a uniting tool because it neglects many social injustices that need to be addressed.